Evolution of Root Morphology in Table Beet: Historical and Iconographic - Goldman, Irwin L.; Janick, Jules (Frontiers in Plant Science, 2021)
The Beta vulgaris complex includes sugar beet, mangel wurzel, Swiss chard, fodder beet and table beet. The table beet was derived from the wild sea beet, Beta vulgaris (L.) subsp. maritima (L.) Arcang, with small non-spherical roots. Table beet is presently a popular vegetable cultivated for its pigmented roots, typically red but also yellow and other colors. Wild forms were consumed in antiquity mainly for their leaves with roots used medicinally. Beet is referred to in the Septuagint, a Greek translation of the first five books of the Hebrew bible, made in Ptolomeic Egypt in the third century BCE. A beet identified as Beta maritima is included in De Material Medicus of Pedanius Dioscorides written in the first century CE and the first illustrated version of 512, known as the Juliana Anicia Codex, includes an image with non-spherical root. Beet is mentioned in several tractates of the Talmud, a 6th century collection of history and civil law written in Babylonia. Beta maritima possesses supernumerary root cambia, which facilitated selection of swollen rooted forms. The first colored illustration of swollen rooted table beet, Beta vulgaris, can be found in the 1515-1517 frescos of Raphael Sanzio and Giovanni Martina da Udine in the Villa Farnesina in Rome. Swollen roots in Roman beet are illustrated and described in the 1587 French herbal Historia Generalis Plantarum of Jacques Dalechamps. Conically-shaped beet roots are found in the market painting of Franz Snijders in the 17th century. Various spherical forms of beet root are found in the work of American painter James Peale in 1826. A complete array of beet root types is found in the Benary catalog of 1876. Modern, spherical beet roots were depicted in 1936 by the Russian painter Zinaida Serebriakov. Artistic and historical representations of table beet suggest that swollen rooted forms have existed during the past five centuries, but conically-shaped roots were gradually replaced by spherically-shaped roots during this period.